2005
DOI: 10.1073/pnas.0407266102
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 BRC motifs bind RAD51–DNA filaments

Abstract: Germ-line mutations in BRCA2 account for approximately half the cases of autosomal dominant familial breast cancers. BRCA2 has been shown to interact directly with RAD51, an essential component of the cellular machinery for homologous recombination and the maintenance of genome stability. Interactions between BRCA2 and RAD51 take place by means of the conserved BRC repeat regions of BRCA2. Previously, it was shown that peptides corresponding to BRC3 or BRC4 bind RAD51 monomers and block RAD51-DNA filament form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 45 publications
5
118
1
3
Order By: Relevance
“…In mammals, the BRC repeats are involved in the interaction of Brca2 with Rad51 (Wong et al, 1997;Chen et al, 1998b;Davies et al, 2001;Galkin et al, 2005). Since an interaction between Brca2 and Dmc1 has never been described in any other organism than Arabidopsis (to our knowledge), there is no clue about the region of Brca2 that is involved in binding to Dmc1.…”
Section: Atrad51 and Atdmc1 Interact Together Or With Their Human Coumentioning
confidence: 84%
See 1 more Smart Citation
“…In mammals, the BRC repeats are involved in the interaction of Brca2 with Rad51 (Wong et al, 1997;Chen et al, 1998b;Davies et al, 2001;Galkin et al, 2005). Since an interaction between Brca2 and Dmc1 has never been described in any other organism than Arabidopsis (to our knowledge), there is no clue about the region of Brca2 that is involved in binding to Dmc1.…”
Section: Atrad51 and Atdmc1 Interact Together Or With Their Human Coumentioning
confidence: 84%
“…Yang et al (2002) demonstrated that a DNA-binding domain is present in the 800-amino acid C-terminal region of Brca2 that can stimulate Replication Protein A (RPA)-dependent strand transfer between homologous DNA molecules by Rad51; this region could only be crystallized in the presence of Dss1, which allowed the authors to define domains in this C-terminal region of Brca2 that were involved in binding Dss1. Work from Galkin et al (2005) also indicates that the BRC motifs number 3 and number 4 in human Brca2 can form stable complexes with Rad51-DNA nucleoprotein filaments. They also reveal the regions in Rad51 that are involved in contacting the BRC motifs.…”
mentioning
confidence: 99%
“…The BRC4 peptide was found to disrupt RAD51 filaments, presumably by binding RAD51 monomers in solution, thereby shifting the equilibrium towards BRC4-RAD51 heterodimer formation (Davies and Pellegrini, 2007;Esashi et al, 2007). However, this disruptive effect was only observed when BRC4 was present in molar excess compared to RAD51, and at lower concentrations of BRC4 it was found to associate with RAD51 filaments formed on dsDNA in the presence of the non-hydrolysable ATP analogue 5 0 -adenylyl-b, g-imidodiphosphate (AMP-PNP) (Galkin et al, 2005). When similar experiments were carried out with BRC3, it was found that excess BRC3 could again dissociate RAD51 filaments, but only in the presence of ATP, while sub-stoichiometric amounts of BRC3 were found to form stable associations with the RAD51 filaments.…”
Section: Regulation Of Recombination By Brca2 T Thorslund and Sc Westmentioning
confidence: 99%
“…When similar experiments were carried out with BRC3, it was found that excess BRC3 could again dissociate RAD51 filaments, but only in the presence of ATP, while sub-stoichiometric amounts of BRC3 were found to form stable associations with the RAD51 filaments. In the presence of a non-hydrolysable ATP analogue, BRC3 could form stable associations with the RAD51 filaments even when in excess over RAD51 (Galkin et al, 2005). That the different BRC motifs are non-equivalent in their ability to interact with RAD51 is further strengthened by the observation that a single mutation in RAD51-A190V prevents RAD51 interaction with BRC3 but not BRC4 .…”
Section: Regulation Of Recombination By Brca2 T Thorslund and Sc Westmentioning
confidence: 99%
“…The eight BRC repeats share only a core consensus sequence and appear to bind Rad51 with different affinities (10,22,25). In addition, BRC3 and BRC4, which have only 30% identity, appear to interact with Rad51 nonequivalently, with BRC3 binding to the N-terminal domain and BRC4 binding to the nucleotide-binding core domain (25,26).…”
Section: Brc-rpa Fusion Proteins Increase Hdr In Brca2 Mutant Cells Bmentioning
confidence: 99%